Optimization Study of Integrated Scenarios on Cyclic Steam Stimulation (CSS) Using CMG STARS Simulator - Boni Swadesi; Suranto Suranto; Indah Widiyaningsih; Matrida Jani (Journal of Petroleum and Geothermal Technology, 2020)
Reservoirs in the world contain various types of oil, the difference of these oil types can be seen in the viscosity value and also the value of the API degree. Reservoirs in the U-field contain heavy oil that cannot be produced conventionally so we need the EOR (Enhanced Oil Recovery) method. CSS is a method that uses high-temperature hot steam aimed at reducing the viscosity of the oil so that oil can be produced. In this final project, a simulation is conducted to study the effect of various parameters such as steam quality, injection rate, and cyclic period on CSS and also determine the best scenario for U-field. The simulation begins by determining the best steam quality value, then doing sensitivity to the expected injection rate, followed by sensitivity to the cyclic period. The best scenario results are the integration of optimum parameters, namely steam quality 0.8, the injection rate of 550 BPD, and cyclic period of 20 days injection, 4 days soaking, and 60 days of production produce RF of 35.02%.